Using log diaries to examine the activities of final-year medical students at decentralised training platforms of four South African universities - A Dreyer; L Rispel (South African Medical Association, 2022)
Background. An important strategy in the transformation and scaling up of medical education is the inclusion and utilisation of decentralised training platforms (DTPs). Objective. In light of the dearth of research on the activities of medical students at DTPs, the purpose of this study was to determine how final-year medical students spent their time during the integrated primary care (IPC) rotation at a DTP. Methods. The study was conducted at Sefako Makgatho Health Sciences University (SMU), the University of KwaZulu-Natal (UKZN), the University of the Witwatersrand (Wits) and Walter Sisulu University (WSU). At each of the participating universities, a voluntary group of final-year medical students completed a log diary by entering all activities for a period of 1 week during the IPC rotation. The log diary contained five activity codes: clinical time teaching time, skill time, community time and free time, with each subdivided into additional categories. The data were analysed for students at each university separately, using frequencies and proportions. Results. A total of 60 students volunteered to complete the diaries: at WSU n=21; UKZN n=11; Wits n=18; and SMU n=10. At each university, students reported that they spent large amounts of time on clinical activities: WSU=46.0%; UKZN=33.8%; Wits=29.6%; and SMU=44.1%. They reported low amounts of time spent on community-based activities: WSU 0.8%; UKZN 7.6%; Wits 6.8%; and SMU 0.0%. Conclusion. Students reported that they spent a sizeable proportion of their time on clinical activities, while reported time spent on community-based activities was negligible. The transformation potential of DTPs will only be realised when students spend more time on community-based activities.